Consumer Attitudes and Preferences for Fresh Market Tomatoes. Issue 10 (12th September 2014) - Oltman, A.E.; Jervis, S.M.; Drake, M.A.
Abstract This study established attractive attributes and consumer desires for fresh tomatoes. Three focus groups (n = 28 participants) were conducted to explore how consumers perceived tomatoes, including how they purchased and consumed them. Subsequently, an Adaptive Choice Based Conjoint (ACBC) survey was conducted to understand consumer preferences toward traditional tomatoes. The ACBC survey with Kano questions (n = 1037 consumers in Raleigh, NC) explored the importance of color, firmness, size, skin, texture, interior, seed presence, flavor, and health benefits. The most important tomato attribute was color, then juice when sliced, followed by size, followed by seed presence, which was at parity with firmness. An attractive tomato was red, firm, medium/small sized, crisp, meaty, juicy, flavorful, and with few seeds. Deviations from these features resulted in a tomato that was rejected by consumers. Segmentations of consumers were determined by patterns in utility scores. External attributes were the main drivers of tomato liking, but different groups of tomato consumers exist with distinct preferences for juiciness, firmness, flavor, and health benefits.